The world economy and the euro area: Global upswing remains intact for the time being - Ferdinand Fichtner; Guido Baldi; Martin Bruns; Christian Dreger; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Economic Bulletin, 2017)
The global economy is expected to grow by four percent annually over the next two years. This is a slight increase in the German Institute for Economic Research forecast in comparison to that of the fall. The upswing will gain momentum in both developed and emerging economies. Private consumption will play a pivotal supporting role as investment continues to grow rapidly around the globe. Despite the high level of unemployment in some countries, the euro area is experiencing stable growth, though its investment could be more dynamic. In China, cutting back overcapacity in manufacturing should suitably curb expansion. And a somewhat less expansive monetary policy emanating from the USA and euro area could curb worldwide demand to the extent that global economic growth does not continue to accelerate. Political uncertainty in Europe and the USA, as well as potential trade restrictions, pose the primary risks to the world economy.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook